Communication and sport surveying the field - Billings, Andrew C.; Butterworth, Michael L.; Turman, Paul D. (SAGE, 2015)
Examines a wide array of topics necessary for students to understand sports media, rhetoric, culture, and organizations from micro to macro-level issues. Everything from youth to amateur to professional sports is addressed through varied useful lens such as mythology, community, and identity.